Labor tenancy and social change in rural Natal society, 1920s to 1940s - Wardrop, Joan (African Studies Assocation of Australasia and the Pacific, 2004)
Review of McClendon, Thomas V. 2002. Genders and generations apart: Labor tenants and customary law in segregation-era South Africa, 1920s to 1940s. Portsmouth NH, USA: Heinemann. ISBN: 0-325-07088-1, 0-85255-956-9 (Cloth); 0-325-07110-1, 0-85255-955-0 (P/b).